Unmasking Nepal's Public Service Riddles: The Paradox of Communication Dynamics - Shamim, Saemah (Journal of Contemporary Sociological Issues, 2025)
Nepal's public service system faces significant challenges in effectively addressing citizen grievances. This study examines how Public Service Management operates as a Grievance Redressal Mechanism (GRM) within the Communication and Information Service. Utilizing a descriptive qualitative research design that involved five informants and a mixed-methods approach for data analysis, this research delves into the complexities of public service delivery in Nepal. Key findings highlight critical gaps in direct evidence, reliability, responsiveness, assurance, and empathy within the GRM. These deficiencies obstruct effective grievance redressal and undermine public trust. This study enriches the literature by providing a nuanced understanding of the challenges encountered by Nepal's public service sector and offers recommendations for enhancing grievance handling mechanisms. Keywords. Management, Public service, Nepal, Grievance Redressal Mechanism